Influência da experiência do operador e da técnica de obtenção de molde na percepção do paciente e veracidade dos modelos em escaneamentos de arco total: estudo in vivo - Dolenkei, Karen Katlein (2023)
With the aim of improving care, facilitating the execution of procedures and generating greater comfort for the patient, today in the dental market we can find different types of scanners, with different formats and software, which can raise doubts for the professional who wants to work with this technology. The aim of this in vivo study was to evaluate the patient's perception of different techniques for obtaining impressions and the operator's experience, in addition to analyzing the time taken to obtain the impressions, the size of the files generated and the veracity of the models obtained. The research subjects (n=15) underwent full-arch scanning by two operators (low and high experience) using two types of intraoral scanners (Trios 3; 3Shape/Virtuo-Vivo; Straumann) and molded by an operator using material elastic band (Hydrogum V; Zhermack) to obtain a plaster model scanned by a benchtop scanner (inEos X5; Dentsply Sirona). The perception of the participants in relation to the procedures was collected through a closed questionnaire. The time to obtain the mold and the size of the files were recorded. Veracity was evaluated using 3D analysis software (Geomagic Control; 3D Systems). For the analysis of the questionnaire, the Mann-Whitney and Chi-square tests were used. For analysis of time to obtain the mold, file sizes and veracity, ANOVA and Tukey HSD tests were used. Pearson correlation was performed between file size and scanning time. In the analysis of the patient's perception, significant differences were verified in relation to comfort, the Virtuo Vivo scanner received a better evaluation (P<.001) and the operator with more experience was better evaluated with both scanners (P<.001). No significant differences were found regarding patient preference regarding the technique for obtaining full-arch models (conventional vs. digital) (P>.001). For scanning and impression time, there was a significant difference in the total time (maxilla/mandible) (P<.001), with Trios 3 presenting the shortest time (P=.042). In the individual analysis, the conventional impression took longer for the maxilla and mandible (P<.001), with no difference between the scanners (P>.001). The less experienced operator took longer for the scans (P< .001). Operator experience did not affect scan file sizes (P>.001), however the scanner did, with Trios 3 producing larger files and Virtuo Vivo having greater dispersion. Largest files were always found for the maxilla (P<.001) and the inEos benchtop scan generated the largest files among the three scanner systems (P<.001). For the analysis of veracity between the models, no significant difference was found between the different techniques, between the scanners and between the operators (P>.001). The correlation between scanning time and file size was positive but weak, regardless of scanner and operator. There was no preference for the technique for obtaining the full-arch models, but the patient's experience was influenced by the operator and scanner. Scanning times and file sizes varied between scanners. Both techniques (conventional/digital) and scanners showed similar veracity for obtaining full arch models for different operators.